The Synergistic Enhancing-Memory Effect of Donepezil and S 38093 (a Histamine H3 Antagonist) Is Mediated by Increased Neural Activity in the Septo-hippocampal Circuitry in Middle-Aged Mice - Sors, Aurore; Krazem, Ali; Kehr, Jan; Yoshitake, Takashi; Dominguez, Gaelle; Henkous, Nadia; Letondor, Claire; Mocaer, Elisabeth; Béracochéa, Daniel J. (Frontiers in Pharmacology, 2016)
Donepezil, an acetylcholinesterase inhibitor, induces only moderate symptomatic effects on memory in Alzheimer’s disease patients. An alternative strategy for treatment of cognitive symptoms could be to act simultaneously on both histaminergic and cholinergic pathways, to create a synergistic effect. To that aim, 14 month –old C57/Bl6 mice were administered per oesophagy during 9 consecutive days with Donepezil (at 0.1mg/kg and 0.3mg/kg) and S 38093 (at 0.1 mg/kg, 0.3 mg/kg and 1.0 mg/kg), a H3 histaminergic antagonist developed by Servier, alone or in combination and tested for memory in a contextual memory task that modelized the age-induced memory dysfunction. The present study shows that the combination of Donepezil and S 38093 induced a dose-dependent synergistic memory-enhancing effect in middle-aged mice with a statistically higher size of effect never obtained with compounds alone and without any pharmacokinetic interaction between both compounds. We demonstrated that the memory-enhancing effect of the S 38093 and Donepezil combination is mediated by its action on the septo-hippocampal circuitry, since it canceled out the reduction of CREB phosphorylation (pCREB) observed in these brain areas in vehicle-treated middle-aged animals. Overall, the effects of drug combinations on pCREB in the hippocampus indicate that the synergistic promnesiant effects of the combination on memory performance in middle-aged mice stem primarily from an enhancement of neural activity in the septo-hippocampal system.